Adiposity and risk of death: A prospective cohort study of 463, 002 adults. Issue 4 (April 2021) - Yu, Tsung; Bo, Yacong; Chang, Ly-yun; Liu, Xudong; Tam, Tony; Lao, Xiang Qian
Summary: Background: It is crucial to have simple and appropriate measures to identify people with adiposity-related risk. We compared the associations of mortality with body mass index (BMI), waist circumference (WC), waist-to-height ratio (WHtR), and body fat percentage (BF%) in a prospective cohort. Methods: A total of 463, 002 adults were recruited between 1996 and 2017. Vital data were obtained from the National Death Registry System in Taiwan. Cox proportional hazards model was used to assess the associations of BMI, WC, WHtR, and BF% with mortality. Result: Clear U-shape relationships were observed for all four parameters. In both men and women, the lowest risk of mortality was observed in the BMI category of 23.5–24.9 kg/m 2 . Regarding WC, men in the third quintile (79.0–82.9 cm) and women in the fourth quintile (70.0–74.9 cm) had the lowest risk of mortality. For WHtR, men in the third quintile (0.46–0.49) and women in the fourth quintile (0.45–0.48) had the lowest risk of mortality. For BF%, both men and women in the fourth quintile (24.0–27.2% and 28.7–32.8%, respectively) had the lowest risk of mortality. The WC, WHtR, and BF% exhibited slightly associations with the risk of mortality across the three BMI categories [low (10.8–20.9 kg/m 2 ), normal (21.0–27.4 kg/m 2 ) and high (27.5–51.7 kg/m 2 )]. C-statistics of the four parameters ranged from 0.51 to 0.69. Conclusion: Our results suggest that BMI should remain the primary marker for screening excessive adiposity. However, our findings also support the use of the WC, WHtR, and/or BF%, in addition to BMI when assessing the risk of mortality.